(untitled) (International journal of medical sciences, 2026)
Cardiotocography (CTG) is a key method for evaluating fetal condition, providing vital information on fetal heart rate and activity. It is widely applied in clinical settings for monitoring the fetus during pregnancy and labor. Different types of CTG are employed depending on risk factors. Understanding CTG principles and accurate result interpretation helps improve birth outcomes and determine optimal labor management strategies. CTG records made during labor serve as medical documentation, aiding in comprehensive birth assessments and providing legal protection for healthcare providers in complex cases.